Moderators of the Relationship Between Work-Family Conflict and Career Satisfaction - Martins, Luis L.; Eddleston, Kimberly; Veiga, John F. (Academy of Management Journal, 2002)
In this study, we examined the moderating effects of individual differences and sources of support on the negative relationship between work-family conflict and career satisfaction. Data from 975 managers indicated that the relationship was significant for women irrespective of age but was significant for men only in later career. Moreover, the relationship was stronger for individuals who were in the minority gender in their work groups, but it was weaker for those who had strong community ties. Implications are discussed.